Regulation of PfEMP1-VAR2CSA translation by a Plasmodium translation-enhancing factor (2017)
Pregnancy-associated malaria commonly involves the binding of Plasmodium falciparum-infected erythrocytes to placental chondroitin sulfate A (CSA) through the PfEMP1-VAR2CSA protein. VAR2CSA is translationally repressed by an upstream open reading frame. In this study, we report that the P. falciparum translation enhancing factor (PTEF) relieves upstream open reading frame repression and thereby facilitates VAR2CSA translation. VAR2CSA protein levels in var2csa-transcribing parasites are dependent on the expression level of PTEF, and the alleviation of upstream open reading frame repression requires the proteolytic processing of PTEF by PfCalpain. Cleavage generates a C-terminal domain that contains a sterile-alpha-motif-like domain. The C-terminal domain is permissive to cytoplasmic shuttling and interacts with ribosomes to facilitate translational derepression of the var2csa coding sequence. It also enhances translation in a heterologous translation system and thus represents the first non-canonical translation enhancing factor to be found in a protozoan. Our results implicate PTEF in regulating placental CSA binding of infected erythrocytes. © 2017 Macmillan Publishers Limited. All rights reserved.